Analisis Efisiensi Teknis Industri Perabot di Kecamatan Jeumpa Kabupaten Bireuen dengan Data Envelopment Analysis (DEA) Method - Devi Andriyani; Munandar Munandar; Fuadi Fuadi (Jurnal EMT KITA, 2020)
This study aims to determine the technical efficiency of input use (investment value, raw material value and labor cost) on the output (production value) of the furniture industry in Jeumpa sub-district, Bireuen Regency. The sample used is 53 industrial units which are all furniture industry units in Jeumpa District, Bireuen Regency. The data analysis method uses the Data Envelopment Analysis (DEA) analysis tool with the VRS approach. The results showed that only 30 units of furniture industry in Jeumpa District were efficient in using input, while 23 other industrial units had not been able to achieve efficiency in input use.